2002
DOI: 10.1016/s0024-3205(01)01552-1
|View full text |Cite
|
Sign up to set email alerts
|

The herbal medicine Dai-kenchu-to and one of its active components [6]-shogaol increase intestinal blood flow in rats

Abstract: The present study investigated the effects of the herbal medicine Dai-kenchu-to (DKCT) and its 4 individual ingredients on intestinal blood flow (IBF) in rats by laser Doppler flowmetry. Intraduodenal administration of DKCT (30, 100 and 300 mg/kg) increased IBF in a dose-dependent manner, whereas the mean arterial blood pressure was not affected. One of the ingredients in DKCT is dried ginger rhizome (150 mg/kg), whose main component is [6]-shogaol (2 mg/kg), both of which showed similar effects to those shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 17 publications
1
68
1
1
Order By: Relevance
“…DKT seems to exert a fine regulation of intestinal motility safely by eliciting both contraction (excitatory nerves) and relaxation (inhibitory nerves) of smooth muscles without changing the properties of pacemaker potentials. Furthermore DKT increase blood flow in mesenteric artery via releasing CGRP (Murata et al, 2002) and inhibit COX2 activity (Hayakawa et al, 1999a). These effects may protect ICC from inflammation and maintain the normal function of ICC in gastrointestinal disease (Lu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DKT seems to exert a fine regulation of intestinal motility safely by eliciting both contraction (excitatory nerves) and relaxation (inhibitory nerves) of smooth muscles without changing the properties of pacemaker potentials. Furthermore DKT increase blood flow in mesenteric artery via releasing CGRP (Murata et al, 2002) and inhibit COX2 activity (Hayakawa et al, 1999a). These effects may protect ICC from inflammation and maintain the normal function of ICC in gastrointestinal disease (Lu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…DKT seems to improve postoperative quality of life (QOL) of patients after surgery for gastrointestinal disorders, since it makes possible for patients to shorten their duration of hospitalization (Endo et al, 2006). DKT ameliorates gastrointestinal dysfunction through various effects, such as contraction and relaxation of smooth muscles (Furukawa et al, 1995;Kurosawa et al, 1998;Hayakawa et al, 1999b;Satoh K et al, 2001aSatoh K et al, , 2001bTulimat et al, 2001), increase of blood flow in mesenteric artery (Murata et al, 2002) and anti-inflammatory effects (Hayakawa et al, 1999a). Thus, DKT has functional improvement in intestine.…”
Section: Introductionmentioning
confidence: 99%
“…43) Recently, it has been reported that Daikenchu-to increases intestinal blood flow, which is mainly mediated by CGRP, in rats. 4) In our study, Dai-kenchu-to significantly raised plasma CGRP-IS levels after administration to healthy volunteers. On the other hand, plasma CGRP-IS levels after the administration of Dai-kenchu-to with pirenzepine pretreatment tended to decrease compared with the administration of Dai-kenchu-to alone.…”
Section: Discussionmentioning
confidence: 45%
“…[2][3][4] We confirmed that the administration of Dai-kenchu-to causes significant increases in the levels of motilin, vasoactive intestinal polypeptide (VIP), serotonin, calcitonin gene-related peptide (CGRP), and substance P in human plasma. [5][6][7] These results indicate that the gastrointestinal motor activity of Dai-kenchu-to is closely related to changes in these neuropeptides in human plasma.…”
mentioning
confidence: 62%
See 1 more Smart Citation